Чисельний аналіз фільтраційних течій в кусково-однорідному ґрунті методом R-функцій - Подгорний, О. Р. (ХНУРЕ, 2019)
The problem of calculating the porous media flow in piecewise-homogeneous soil is considered. For its numerical analysis it is proposed to use the R-functions method. shows the results of a computational experiment for a test problem.
Keywords: фільтраційні течії; кусково-однорідний ґрунт; течії рідини; задача стаціонарної безнапірної фільтрації; коефіцієнт фільтрації